Hubungan Tingkat Kecemasan dengan Frekuensi Hubungan Seksual pada Ibu Menopause di Desa Ramban Kulon Kecamatan Cermee Kabupaten Bondowoso - Makrifah, Syariatul; Hikmawati, Nova; Suhartin, Suhartin (Universitas Nurul Jadid, 2024)
Menopause is caused by the decline in ovarian function due to aging, which leads to a decrease in estrogen production. This condition results in both physical and psychological changes, leading to various menopausal complaints. The aim of this study was to examine the relationship between anxiety levels and sexual frequency in menopausal women in Ramban Kulon Village, Cermee District, Bondowoso Regency. This research used a quantitative design with a correlational approach and a cross-sectional method. The population consisted of all menopausal women aged 45-59 years in Ramban Kulon Village, totaling 462 individuals. A sample of 82 respondents was selected using random sampling. Data were collected using a questionnaire and analyzed using SPSS with the Spearman Rank test. The results showed that the majority of respondents (31.7%) experienced no anxiety, and most respondents (40.2%) reported low or no sexual activity. The Spearman Rank test yielded a significance value (Asymp. Sig) of 0.000 < 0.05, indicating a significant relationship between anxiety levels and sexual frequency in menopausal women in Ramban Kulon Village. This study confirms the hypothesis and suggests that reducing anxiety may help menopausal women maintain sexual desire during this stage of life.